THE DIFFICULTIES OF EARLY DIAGNOSIS AND TREATMENT OF BOTULISM - V. V. Nikiforov; Yu. N. Tomilin; T. Ya. Chernobrovkinya; Y. D. Yankovskaya; S. V. Burova (SINAPS LLC, 2019)
The popularity of home canning contributes to a sufficiently high incidence of botulism worldwide. The canned products containing botulinum toxin do not change neither color, taste, nor smell of contents of canned food. The criteria for the severity of the course of botulism are considered a violation of swallowing liquid food and symptoms of difficulty breathing. A distinctive feature of the paralytic syndrome in botulism is its symmetry and the absence of a violation of sensitivity. The criteria of the severity of the course of botulism is considered a violation of swallowing liquid food and the severity of acute respiratory failure. The paper presents the features of the therapy of the patients with botulism in the intensive care unit. Clinical examples illustrate the difficulties in recognizing botulism at the early stage of the disease, which are due to the polymorphism of the clinical picture of botulism and the similarity of symptoms with other diseases. Most commonly, patients with botulism are diagnosed with acute intestinal infection or the neurological pathology. Patients are not hospitalized in a timely manner, which can affect the outcome of the disease. The ability to recognize botulism at the prehospital stage is necessary for all doctors.